2020
DOI: 10.1371/journal.pone.0239277
|View full text |Cite
|
Sign up to set email alerts
|

Robo-investment aversion

Abstract: In five experiments ( N = 3,828), we investigate whether people prefer investment decisions to be made by human investment managers rather than by algorithms (“robos”). In all of the studies we investigate morally controversial companies, as it is plausible that a preference for humans as investment managers becomes exacerbated in areas where machines are less competent, such as morality. In Study 1, participants rated the permissibility of an algorithm to autonomously exclude morally co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 53 publications
3
25
2
1
Order By: Relevance
“…In this paper we ask whether this effect is greater in women. Preliminary evidence comes from our earlier study (Niszczota and Kaszás, 2020), in which participants assessed their attitudes toward fourteen controversial industries from Trinks and Scholtens (2017). While analyzing our data, we observed that women felt significantly less comfortable with the perspective of investing in each of the controversial industries (see Fig.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…In this paper we ask whether this effect is greater in women. Preliminary evidence comes from our earlier study (Niszczota and Kaszás, 2020), in which participants assessed their attitudes toward fourteen controversial industries from Trinks and Scholtens (2017). While analyzing our data, we observed that women felt significantly less comfortable with the perspective of investing in each of the controversial industries (see Fig.…”
Section: Introductionmentioning
confidence: 54%
“…Such shifts in the composition of investors and corporate decision-makers might become tipping points, just as the number of "green" investors in the investor populationthat find severe pollution by a company to be unacceptable -might determine whether a company reforms or not (Heinkel et al, 2001). The left panel shows data from an earlier study (Niszczota and Kaszás, 2020) on which the current study is based on (14 sin industries from Trinks and Scholtens 2017), and the right panel shows data for the current study (7 sin industries with which participants felt the least comfortable with in the earlier study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Study 1, we have asked participants to consider investment in seven morally controversial industries (involved in abortion/abortifacients, adult entertainment, animal testing, controversial weapons, fur, gambling, tobacco) and seven conventional industries (involved in air freight/logistics, construction/engineering, household durables, marine transport, road/rail transport, semiconductors/semiconductor equipment, water utilities); these were used in previous research [ 4 , 21 ], but to aid readability the descriptions are provided in the S1 Appendix . More specifically, participants assessed the moral appropriateness of investing in industries ( Would it be morally appropriate if you invested in companies from the following industries ?…”
Section: Methodsmentioning
confidence: 99%
“…In Study 1, we have asked participants to consider investment in seven morally controversial industries and seven conventional industries used in previous research Niszczota and Kaszás, 2020). More specifically, participants assessed the moral appropriateness of investing in industries (Would it be morally appropriate if you invested in companies from the following industries?…”
Section: Methodsmentioning
confidence: 99%